A Força Expedicionária Brasileira – FEB : em busca dos "pracinhas" negros nos livros didáticos de história : (1944-1945) - Santos, Adão Silvio dos (2021)
The present research work formulated a study on the Brazilian Expeditionary Force, known by the acronym FEB, the military expedition organized by Brazil, with the support of the United States of America, to fight at the end of World War II, in the battlefields of Italy, from 1944 to 1945. Based on the bibliographical analysis and testimonies of small towns from Mato Grosso who participated in this conflict in Italy, from 1944 to 1945, it was possible to probe their interactions and experiences with the Italian population during this period under study. In addition, it carries out an analysis of textbooks on History of Elementary and High School, with the objective of observing the participation of Brazilian practitioners, essentially seeking the presence of black ex-combatants who made up the ranks of the Brazilian Expeditionary Force - FEB. As a product, required by the Professional Master's Degree in History - PROFHISTÓRIA, a mobile application was developed to serve as a didactic-pedagogical resource to help teachers in the classroom and other extra activities, containing the history and images about the FEB and the performance of practitioners blacks in World War II.